use Option elimination technique,u will get A

1,066 views

0 votes

Let’s assume one part of 50 is $x$,then other will be $(50-x)$

Now according to the question sum of reciprocal is $\frac{1}{12}$

$\implies \frac{1}{x}+\frac{1}{(50-x)}=\frac{1}{12}$

$\implies \frac{50-x+x)}{x*(50-x)}=\frac{1}{12}$

$\implies 50*12=x*(50-x)$

$\implies 600=50x-x^2$

$\implies x^2-50x+600=0$

$\implies x^2-30x-20x+600=0$

$\implies x(x-30)-20(x-30)=0$

$\implies (x-30)(x-20)$

$\implies x=30,20$

Option (a) is correct.

Now according to the question sum of reciprocal is $\frac{1}{12}$

$\implies \frac{1}{x}+\frac{1}{(50-x)}=\frac{1}{12}$

$\implies \frac{50-x+x)}{x*(50-x)}=\frac{1}{12}$

$\implies 50*12=x*(50-x)$

$\implies 600=50x-x^2$

$\implies x^2-50x+600=0$

$\implies x^2-30x-20x+600=0$

$\implies x(x-30)-20(x-30)=0$

$\implies (x-30)(x-20)$

$\implies x=30,20$

Option (a) is correct.